2012
DOI: 10.1097/ccm.0b013e318241e51e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neighborhood poverty rate and bloodstream infections in the critically ill*

Abstract: Within the limitations of our study design, increased neighborhood poverty rate, a proxy for decreased socioeconomic status, appears to be associated with risk of bloodstream infection among patients who receive critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 99 publications
2
27
1
Order By: Relevance
“…Analogously, Mendu et al (2012) elucidated that neighborhoods with greater than 20% poverty rates had 32% increased odds of community-acquired infections compared to those with neighborhood poverty rate <5%. 18 Additionally, we found that race was a significant determinant in regional disparities of sepsis mortality. Many epidemiolgic studies based on hospital discharge records have reported that black persons have higher rates of sepsis, hospitalization mortality, and are twice as likely to develop sepsis as white persons.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Analogously, Mendu et al (2012) elucidated that neighborhoods with greater than 20% poverty rates had 32% increased odds of community-acquired infections compared to those with neighborhood poverty rate <5%. 18 Additionally, we found that race was a significant determinant in regional disparities of sepsis mortality. Many epidemiolgic studies based on hospital discharge records have reported that black persons have higher rates of sepsis, hospitalization mortality, and are twice as likely to develop sepsis as white persons.…”
Section: Discussionmentioning
confidence: 76%
“…18-21 Numerous studies have shown that uninsured critically ill patients are less likely to receive life-saving critical care procedures, receive less post acute care during critical illness recovery, and have increased mortality compared to those with insurance. 22-27 As seen in our study, strongly clustered counties had greater socioeconomic and access to care disparities.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 38,917 ICU admissions at 2 academic hospitals in Boston, neighbourhood poverty rate was not associated with 30-day, 90-day, 365-day, or hospital mortality [15]. However, within this same cohort, patients living in neighborhoods with high poverty rates were significantly more likely to have positive blood cultures within 48 hours of admission to ICU [16]. Neighbourhood poverty rate was ascertained using residential addresses and thus individuals without a fixed address were systematically excluded from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found correlations between a wide range of neighborhood social characteristics and health care outcomes [1923]. Using the percentage of African American residents by ZIP code as the primary predictor variable, Rodriguez et al [21] analyzed the time from day 90 of end-stage renal disease to death from any cause and time to first renal transplantation of adult dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Colvin et al [22] further emphasized the effect of SES on mortality by showing an inverse linear association between SES and in-hospital pediatric mortality. In adult patients with critical illness, Mendu et al [23] found that neighborhood poverty rate was associated with blood stream infection near critical care initiation. The adjusted risk of community-acquired bloodstream infection was 1.32 (95 % CI 1.11–1.56; p = 0.002) and 1.51 (95 % CI 1.04–2.20; p = 0.03) for patients from neighborhoods with 20–40 and >40 % poverty rates, respectively, compared to patients with a neighborhood poverty rate <5 %.…”
Section: Introductionmentioning
confidence: 99%